Growth and development of blackgram (Vigna mungo) under foliar application of Panchagavya as organic source of nutrient - and P.Saranraj, R. Suresh Kumar, P. Ganesh, K. Tharmaraj (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The present study was aimed to improve the growth and development of Blackgram (Vigna mungo) under foliar application of panchagavya as organic nutrient. A pot culture experiment was conducted at the Experimental farm during March-May 2010 season to evaluate the efficacy of Panchagavya foliar spray and NPK on the physiological growth and yield of Blackgram (Vigna mungo) cv. ADT-3. The results of the experiment revealed that foliar application of Panchagavya recorded significant improvement in chlorophyll content, N content of root nodules, plant height, number of branches per plant, leaf area index (LAI) and dry matter production when compared with NPK and control. Yield attributes such as number of pods per plant, number of seeds per pod, test weight and grain yield were also recorded significantly higher under foliar application of Panchagavya over NPK and control. Three percent Panchagavya foliar spray given at 15th, 25th, 35th and 45th days of interval period recorded significantly higher growth and yield of Blackgram than NPK and untreated control.